Disaster Preparedness and Readiness of an Institution in one ASEAN Country - Russell John N Panes; Ilyn K Panes; Randy Joy M Ventayen; Jeff G Pereyras; Caren C Orlanda-Ventayen (ASEAN Multidisciplinary Research Journal, 2020)
Disaster preparedness and readiness are important in institutions to prevent damage to property and to safeguard the life of students. The purpose of this paper is to know the level of readiness of the public secondary school in Bangkok specifically in Wat Dusitaram Secondary School on disaster risk reduction and management. This study dealt with disaster risk reduction and management of the public secondary schools in Bangkok. It descriptive survey research which use the survey method of research. Data were gathered, tabulated and analyzed. The total respondents are from the regular teachers of Wat Dusitaram Secondary school where disaster risk reduction and management being measured. Female teachers dominated the total number of respondents. The teachers have a favorable attitude that serves as a second mother in school, and their knowledge and skills on disaster risk reduction management are being measured. The level of readiness and level of participation towards disaster risk reduction and management are used. All schools should be given drills and training on disaster risk reduction and management to develop their skills and knowledge when it comes to the disaster that may occur in school.